Non-invasive ventilation for the management of acute hypercapnic respiratory failure due to exacerbation of chronic obstructive pulmonary disease - Osadnik,CR; Tee,VS; Carson-Chahhoud,KV; Picot,J; Wedzicha,JA; Smith,BJ (Cochrane Database of Systematic Reviews, 2017)
BackgroundNon-invasive ventilation (NIV) with bi-level positive airway pressure (BiPAP) is commonly used to treat patients admitted to hospital with acute hypercapnic respiratory failure (AHRF) secondary to an acute exacerbation of chronic obstructive pulmonary disease (AECOPD).ObjectivesTo compare the efficacy of NIV applied in conjunction with usual care versus usual care involving no mechanical ventilation alone in adults with AHRF due to AECOPD. The aim of this review is to update the evidence base with the goals of supporting clinical practice and providing recommendations for future evaluation and research.Search methodsWe identified trials from the Cochrane Airways Group Specialised Register of trials (CAGR), which is derived from systematic searches of bibliographic databases including the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), the Allied and Complementary Medicine Database (AMED), and PsycINFO, and through handsearching of respiratory journals and meeting abstracts. This update to the original review incorporates the results of database searches up to January 2017.Selection criteriaAll randomised controlled trials that compared usual care plus NIV (BiPAP) versus usual care alone in an acute hospital setting for patients with AECOPD due to AHRF were eligible for inclusion. AHRF was defined by a mean admission pH < 7.35 and mean partial pressure of carbon dioxide (PaCO2) > 45 mmHg (6 kPa). Primary review outcomes were mortality during hospital admission and need for endotracheal intubation. Secondary outcomes included hospital length of stay, treatment intolerance, complications, changes in symptoms, and changes in arterial blood gases.Data collection and analysisTwo review authors independently applied the selection criteria to determine study eligibility, performed data extraction, and determined risk of bias in accordance with Cochrane guideline